Faith in Transition: The Complex Interplay of Parent and Peer Influences on Catholic Value Internalization Among College Students - Ott, Joy (Journal for the scientific study of religion, 2026)
Declines in religiosity are often observed during the college years, perhaps due to decreases in parental oversight and increases in peer influence. We explored the role of parent, peer, and school (Catholic or secular) experiences on religiosity (beliefs and behavior) among 270 Catholic students as mediated through introjected and identified internalization. Internalization is a process whereby individuals acquire and assimilate values, ranging from relatively superficial adoption (i.e., introjection) to profound integration of values (i.e., identification). Parent experiences predicted internalization and religious beliefs; these associations were moderated by peer experiences and school. Parent experience was significantly associated with belief only for students at a secular university with low levels of peer experience. Importantly, whereas parent experiences predicted both types of internalization, only identified internalization predicted current religious beliefs and behaviors, which suggests that identification leads to stronger correspondence between early religious experiences with parents and later religious beliefs and behaviors.